Improved overall survival in patients with high-grade serous ovarian cancer is associated with CD16a+ immunologic neighborhoods containing NK cells, T cells and macrophages - Nersesian, Sarah; Arseneau, Riley J.; Mejia, Jorge P.; Lee, Stacey N.; Westhaver, Lauren P.; Griffiths, Nigel W.; Grantham, Stephanie R.; Meunier, Liliane; Communal, Laudine; Mukherjee, Avik; Mes-Masson, Anne-Marie; Arnason, Thomas; et al. (Frontiers in Immunology, 2024)
Background: For patients with high grade serous carcinoma of the ovary (HGSC), survival rates have remained static for the last half century. Despite the presence of tumor mutations and infiltration of immune cells, existing immunotherapies have achieved little success against HGSC. These observations highlight a gap in the understanding of how the immune system functions and interacts within HGSC tumors.We analyzed duplicate core samples from 939 patients with HGSC to understand patterns of immune cell infiltration, localization, and associations with clinical features. We used high-parameter immunohistochemical/Opal multiplex, digital pathology, computational biology, and multivariate analysis to identify immune cell subsets and their associations with HGSC tumors.We defined six patterns of cellular infiltration by spatially restricted unsupervised clustering of cell subsets. Each pattern was represented to some extent in most patient samples, but their specific distributions differed. Overall (OS) and progression-free survival (PFS) corresponded with higher infiltration of CD16a + cells, and their co-localization with macrophages, T cells, and NK cells, on of six cellular neighborhoods that we defined with our spatial assessment.Conclusions: Immune cell neighborhoods containing CD16a+ cells are associated with improved OS and PFS for patients with HGSC. Patterns of immunologic neighborhoods differentiate patient outcomes, and could inform future, more precise approaches to treatment.